Cytomegalovirus and other common enteric viruses are not commonly associated with NEC. (31st August 2015) - Skeath, Thomas; Stewart, Christopher; Waugh, Sheila; Embleton, Nicholas; Cummings, Stephen; Berrington, Janet
Abstract: Aim: Changes in gut microbiota may contribute to NEC, but most studies focus on bacteria. Case reports suggest a link between cytomegalovirus (CMV) or other enteric viruses and NEC, but there are few case series systematically looking at common potential viral causes. We aimed to assess the presence of candidate viruses in blood or stool of a case series of infants with NEC managed in one surgical centre. Methods: We identified 22 infants diagnosed with NEC (from November 2011 to March 2014): 17 had suitable blood stored, of whom 14 also had suitable stool samples stored. Blood was analysed with polymerase chain reaction (PCR) for CMV, Epstein–Barr virus (EBV) and adenovirus, and stool by PCR for norovirus, sappovirus, astrovirus, adenovirus and rotavirus. Results: All samples were negative. Conclusion: Although case reports indicate an episodic association of enteric viruses in NEC, the inability to detect any of these viruses in our 17 NEC infants suggests that a viral aetiology is unlikely to be causative for most sporadic forms of NEC.